Social Functioning of People with HIV/ AIDS (PLWHA) Receiving Antiretroviral Therapy in the City of Bengkulu - Dita Haryani (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The problem in the research is the low number of people with HIV/AIDS (PLWHA) who take antiretroviral drug therapy in Bengkulu City. This occurs because of shame and fear of being stigmatized and discriminated against if other people find out about their status, causing their social functioning to be disrupted (Social Dyscpunction). The purpose of the study was to determine the benefits of antiretroviral drug therapy for people with HIV/AIDS (ODHA) in Bengkulu City on their social functioning. The research uses applied research methods, this research approach uses qualitative research. The research informants were 8 people with HIV/AIDS (ODHA), determined by the snowball sampling technique because the group or person as an informant could not be identified. Data collection techniques include observation, in-depth interviews, and documentation. The results of the research show that there are many benefits for people with HIV/AIDS (PLWHA) who take antiretroviral drug therapy in terms of their social functioning. The physical condition is healthier because antiretroviral drug therapy makes the immune system of PLWHA stable so that the development of viruses can be prevented. Psychologically, people with HIV/AIDS (PLWHA) become better because the therapy process provides a lot of knowledge about HIV/AIDS, thus eliminating fear and worry about the disease they suffer from, ultimately making PLWHA more confident and able to socialize and be able to carry out their social roles or functions. Based on the results of the research, researchers recommend that PLWHA with new status should immediately undergo antiretroviral drug therapy. It is also necessary to carry out interventions to empower families to always provide support to PLWHA, and make efforts to prevent and treat depression problems so that PLWHA remains empowered.